A Third Generation Field‐Aligned Current Model. Issue 1 (7th January 2020) - Edwards, Thom R.; Weimer, D. R.; Olsen, Nils; Lühr, Hermann; Tobiska, W. K.; Anderson, B. J.
Abstract: A new empirical model of field‐aligned currents in the Earth's ionosphere has been developed. This model is derived using magnetometer data from the CHAallenging Minisatellite Payload, Ø rsted, and Swarm satellite missions, which has created a database that spans more than 15 years. These data have been associated with solar wind conditions using the Advanced Composition Explorer satellite, as well as the F 10 . 7, S 10 . 7, M 10 . 7, and Y 10 . 7 solar indices. With the wealth of data and associated driving conditions, this model has been developed to reproduce field‐aligned current maps of the ionosphere based on solar wind electric field, interplanetary magnetic field clock angle, dipole tilt angle, solar index, and geographic hemisphere. This model was constructed using a series of spherical cap harmonic analysis fits based on small selections of the overall database. The coefficients of these fits were then used to develop a model that would reproduce these coefficients based on the previously described driving conditions. One of the most notable improvements demonstrated by this model is the ability to show distinct current regions in the ionosphere, particularly with respect to Region 0 currents during northward B z and highly positive or negative B y . Key Points: A new field‐aligned current model based on satellite magnetometer data from the CHAMP, Ørsted, and Swarm missions has been developed Driving response has been updated from previous models and reflects recent findings by Edwards et al. (2017) and Weimer et al. (2017) Comparisons to AMPERE and AMPS total current for a selection of events has been made, and this model has shown comparable results